Nearshoring and farsharing in Europe within the global economy - Filippo Bontadini; Valentina Meliciani; Maria Savona; Ariel Wirkierman (EconPol Forum, 2022)
We distinguish the geographical source and destination of value added contributed by each country-industry to each country-global-value-chain (GVC) from both input sourcing and output destination perspectives. We define indicators that capture the relative intensity of regional vis-à-vis global (i.e., extra-regional) components of foreign value added and employment. Europe is increasingly sourcing value added from within the region ("nearshoring") but exporting value added globally ("farsharing"). European GVCs mostly generate foreign employment outside Europe. In contrast, most of European employment is activated by European GVCs: an important labor market policy implication arguing for more intensive intra-EU trade and integration. Europe and its economic policy should not only focus on the sourcing of value added across production processes, but also on the final demand that generates economic activity in Europe
Keywords: 330